Assessment of healthcare accessibility and travel distance on intrapartum fetal death: a retrospective cohort study - Moterani, Vinicius Cesar [UNESP]; Abbade, Joelcio Francisco [UNESP]; Borges, Vera Therezinha Medeiros [UNESP]; Fonseca, Cecilia Guimaraes Ferreira [UNESP]; Desiderio, Nathalia; Moterani Junior, Nino Jose Wilson; Moterani, Bento Gonsalves (Pan Amer Health Organization, 2023)
Objective. To determine if there was an association between intrapartum stillbirths and both traveled distance for delivery and delivery care accessibility, assessing periods before and during the COVID-19 pandemic.Methods. This is a population-based cohort study. Patients had birth occurring after the onset of labor; the primary outcome was intrapartum stillbirth. City of residence was classified according to the ratio between deliveries performed and total births among its residents; values lower than 0.1 indicated low delivery care accessibility. Travel distance was calculated using the Haversine formula. Education level, maternal age, and birth sex were included. In each period, relative risk was assessed by generalized linear model with Poisson variance.Results. There were 2 267 534 deliveries with birth occurring after the onset of labor. Most patients were between age 20 and 35 years, had between 8 and 11 years of education, and resided in cities with high delivery care accessibility. Low delivery care accessibility increased risk of intrapartum stillbirth in the pre-pandemic (relative risk [RR] 2.02; 95% CI [1.64, 2.47]; p < 0.01) and the pandemic period (RR 1.69; 95% CI [1.09, 2.55]; p = 0.015). This was independent of other risk-increasing factors, such as travel distance and fewer years of education.Conclusions. Low delivery care accessibility is associated with the risk of intrapartum stillbirths, and accessibility reduced during the pandemic. Delivery of patients by family physicians and midwives, as well as official communication channels between primary care physicians and specialists, could improve patient healthcare-seeking behavior.
Keywords: Travel; health services accessibility; time-to-treatment; fetal mortality; Brazil